QUALITY LIFE OF WOMEN WITH HIV/AIDS BASED ON CD4 AND DISCLOSURE HIV STATUS IN BANDUNG AND CIMAHI - Lina Safarina; Oyoh Oyoh (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2014)
Introduction: Women become most vulnerable groups of contracting HIV from a partner or husband. This study aimed to explore the different of quality of life of women with HIV/AIDS based on CD4 levels and exposure status. Method:Sampling technique with purposive sampling, 60 samples were obtained according to criteria. Variable data using the WHO Quality of life (QOL), CD4 levels of data using secondary data and data disclosure using the status of closed questions. Univariate analysis of the frequency distributions and bivariate analysis used t tests. Results: The average of quality of life of respondents with HIV is 82.92 (SD = 4,534), while for respondents with AIDS is 80.45 (SD = 4284).There was statistically significant difference between average quality of life of respondents with HIV with respondents with AIDS (P value = 0.043). Averagequality of life of respondents who did not open status disclosure is 81.07 (SD 4,128), while the open status of respondents openness average quality of life was 85.14 (SD = 4,688). There was statistically significant difference between average quality of life of respondents who openness status is not open to the respondent that the openness of the open status (P value = 0.003). Discussion: Suggestions for nurses were to increase the role in providing motivation for PLHIV women to regularly check the levels of CD4, to assist PLWHA in ARV consumption through home care, as a health educator for PLWHA families and communities and as a researcher in identify measures that can improve the quality of life of women with HIV/AIDS. Keywords: HIV/AIDS, CD4, disclosure of status, Quality of life